Conhecimento dos técnicos em enfermagem de uma unidade de emergência acerca dos cuidados com pacientes disfágicos (Revista Brasileira Multidisciplinar, 2024)
Among eating disorders, oropharyngeal dysphagia is characterized as an alteration that can occur in any part of the digestive tract, from the mouth to the stomach. Therefore, the present study analyzed the understanding of nursing technicians working in the emergency unit of a hospital, regarding the necessary care for patients with dysphagia or at risk of dysphagia. The work is a cross-sectional study, developed during the year 2022, in a teaching hospital, with the application of a questionnaire containing 15 objective and self-administered questions. Although Nursing Technicians have been working for a long time, feel capable of caring for dysphagia patients and know how to conceptualize what dysphagia is, they were unable to identify risk factors and signs or symptoms of dysphagia when questioned. In this way, we conclude that the participants do not adequately understand what dysphagia is, they cannot relate the clinical conditions that offer risk to swallowing and they cannot identify the manifestations of dysphagia that may be presented by the patients. In view of these findings, we can also identify the need for periodic training on the subject of dysphagia among nursing teams that are involved in patient care, especially in emergency units.
Keywords: speech, language and hearing sciences; nursing; deglutition disorders; emergency nursing.